2016
DOI: 10.1007/s12038-016-9601-5
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 inhibition as a therapeutic approach for overcoming multidrug resistance in cancer

Abstract: Breast cancer resistance protein (BCRP, ABCP or MXR)/ATP-binding cassette subfamily G member 2 (ABCG2) was characterized as a multidrug resistance efflux transporter in 1998. ABCG2 physiologically acts as a part of a selfdefence mechanism for the organism; it enhances eliminating of toxic xenobiotic substances and harmful agents in the intestine, as well as through the blood-brain barrier and placenta. ABCG2 recognizes and transports numerous anticancer drugs including conventional chemotherapeutic and new tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 93 publications
0
42
0
Order By: Relevance
“…For example, McDonald et al previously demonstrated that docetaxel-resistant MDA-MB and MCF-7 breast cancer cells developed a cross-resistance to paclitaxel and vincristine (20), concordant to the findings of the present study. Multiple reports have indicated that resistant sublines commonly express MDR-1 and MRP proteins (9,21,22). Clinical studies also report the development of cross-resistance to multiple anticancer agents following the initial success of chemotherapy (23,24), which may also be due to the overexpression of MDR-1 and MRPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, McDonald et al previously demonstrated that docetaxel-resistant MDA-MB and MCF-7 breast cancer cells developed a cross-resistance to paclitaxel and vincristine (20), concordant to the findings of the present study. Multiple reports have indicated that resistant sublines commonly express MDR-1 and MRP proteins (9,21,22). Clinical studies also report the development of cross-resistance to multiple anticancer agents following the initial success of chemotherapy (23,24), which may also be due to the overexpression of MDR-1 and MRPs.…”
Section: Discussionmentioning
confidence: 99%
“…Although certain patients initially respond to these classical cytotoxic drugs, patients exhibit high rates of systemic relapse during early stages and decreased overall survival times following metastasis (6,7). This may be due to drug resistance development arising from the overexpression of drug-efflux pumps, including the multidrug resistance (MDR)-associated transporter P-glycoprotein (MDR-1) or proteins from the MDR-associated protein (MRP) family, collectively members of the ATP-binding cassette (ABC) transporter superfamily (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, ABCG2/breast cancer resistant protein (BCRP) is a well‐defined efflux transporter first identified in a breast cancer cell line selected for resistance to mitoxantrone. Similar to the other MDR transporters, BCRP serves as an efflux pump for many diverse scaffolds of xenobiotics, including 7‐ethyl‐10‐hydroxycamptothecin (SN‐38), tyrosine kinase inhibitors, methotrexate, and is involved in drug resistance in colon, breast cancer, and gastric carcinomas …”
Section: Mechanisms Of Multidrug Resistancementioning
confidence: 99%
“…However, some types of cancer cells overexpress BCRP/ABCG2 and acquire resistance to anticancer drugs, and thus BCRP/ABCG2 holds promise as a potent molecular target in chemotherapy aimed at these cancers. Reports of interaction between several tyrosine kinase inhibitors and BCRP/ABCG2 prompted investigation of many kinds of modulators for their ability to reverse multidrug resistance mediated by BCRP/ABCG2 . Intensive structure–activity relationship studies have identified natural and chemically synthesized flavonoids as promising candidates exhibiting such reversal effects .…”
Section: Introductionmentioning
confidence: 99%